Private Law Publications in Hungary between 1920–1944 with Special Regard to the Influence of German Law and the Restriction of Rights - Krausz, Bernadett (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2022)
The study analyses the reaction of Hungarian private law jurists to the right restrictions and deprivations of the Horthy era concerning Civil law, whether they welcomed or criticized them and more importantly, if they spoke about them at all publicly. I examined the legal papers that were published in the subject period in Hungary, namely the Jogtudományi Közlöny (Journal of Jurisprudence), Polgári Jog (Civil Law) and Magyar Jogi Szemle (Hungarian Law Review) in order to seek answers.